Revision of the genus Eulichas Jacobson, 1913 (Coleoptera: Eulichadidae) I. Introduction, morphology of adults, key to subgenera and species groups, and taxonomy of E. funebris species group - Hájek, Jiří (Zootaxa, 2007)
The predominantly Oriental genus Eulichas Jacobson, 1913, family Eulichadidae, is reviewed in part. The Eulichas funebris species group is revised. A brief history of classification of the genus, as well as the general morphology of the adults, is presented. The following nine new species are described: E. birmanica Hájek, sp. nov. (Myanmar: Tenasserim), E. haucki Hájek, sp. nov. (Thailand), E. jaechi Hájek, sp. nov. (Malaysia), E. janbezdeki Hájek, sp. nov. (Laos); E. kubani Hájek, sp. nov. (Laos, Vietnam), E. meghalayensis Hájek, sp. nov. (India: Meghālaya), E. minuta Hájek, sp. nov. (Sumatra, Nias, Siberut), E. strbai Hájek, sp. nov. (Malaysia), and E. tanahrata Hájek, sp. nov. (Malaysia). A lectotype is designated for E. mediocris (Pic, 1921) (Sumatra).